Pendidikan yang Bercorak Islam di Indonesia II (Abad 21) - Rohman, Ahmad Minanur; Rois, Siti; Kusmawati, Heny (PT Literasi Nusantara Publisher, 2023)
This paper discusses the characteristics of Islamic education and the problems of the future of Islamic education. The purpose is to describe the characteristics of Islamic education in Indonesia in the 21st century. This writing is the result of a literature study sourced from books, articles, and journals. The result of this writing is that the book of the Qur'an has provided rich knowledge of the scientific world and science, this has been proven scientific, and many scientists want to study it. With this proof, it can create an impetus for technology to be involved in the world of science and science. The rapidly growing influence of technology makes it easier for the Islamic education system to be future-orientated. Inadequate Islamic education makes technology must be involved to encourage more advanced education. The world of education really needs technology to be able to develop its existence as a concept, method, model in the learning process. Further results of Islamic education are still found in various problems such as inadequate facilities for educational institutions, the tendency of Islamic education to focus more on social sciences, not on the exact sciences where the exact sciences are a reference for technological progress. Furthermore, education is prioritised in public and private schools, resulting in lower exam pass rates in madrasah schools. The problems faced give the reality that the higher the demand for the master of science and technology and the necessary strengthening of religious teachings.